Systematic review and meta-analysis of metal versus plastic stents for preoperative biliary drainage in resectable periampullary or pancreatic head tumors. Issue 9 (September 2016) - Crippa, S.; Cirocchi, R.; Partelli, S.; Petrone, M.C.; Muffatti, F.; Renzi, C.; Falconi, M.; Arcidiacono, P.G.
Abstract: Background: Preoperative biliary drainage (PBD) with stenting increases complications compared with surgery without PBD. Metallic stents are considered superior to plastic stents when considering stent-related complications. Aim of the present systematic review and meta-analysis is to compare the rate of endoscopic re-intervention before surgery and postoperative outcomes of metal versus plastic stents in patients with resectable periampullary or pancreatic head neoplasms. Methods: We conducted a bibliographic research using the National Library of Medicine's PubMed database, including both randomized controlled trials (RCTs) and non-RCTs. Quantitative synthesis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Statistical heterogeneity was assessed using the I 2 tests. Results: One RCT and four non-RCTs were selected, including 704 patients. Of these, 202 patients (29.5%) were treated with metal stents and 502 (70.5%) with plastic stents. The majority of patients (86.4%) had pancreatic cancer. The rate of endoscopic re-intervention after preoperative biliary drainage was significantly lower in the metal stent (3.4%) than in the plastic stent (14.8%) group (p < 0.0001). The rate of postoperative pancreatic fistula was significantly lower in the meta stent group as well (5.1% versus 11.8%, p = 0.04). The rate of post-operative surgical complications and of – post-operative mortality did not differ between the two groups. Conclusions: Although the present systematic review and meta-analysis demonstrates that metal stent are more effective than plastic stents for PBD in patients with resectable periampullary tumors, randomized controlled trials are needed in order to confirm these data with a higher level of evidence.